In‐Home HIV Testing and Nevirapine Dosing by Traditional Birth Attendants in Rural Zambia: A Feasibility Study. (23rd September 2013) - Brennan, Alana T.; Thea, Donald M.; Semrau, Katherine; Goggin, Caitlin; Scott, Nancy; Pilingana, Portipher; Botha, Belinda; Mazimba, Arthur; Hamomba, Leoda; Seidenberg, Phil
<x xml:space="preserve">Abstract</x> Introduction Access to lifesaving prevention of mother‐to‐child transmission (PMTCT) services is problematic in rural Zambia. The simplest intervention used in Zambia has been 2‐dose nevirapine (NVP) administration in the peripartum period, a regimen of 1 NVP tablet to the mother at the onset of labor and 1 dose in the form of syrup to the newborn within 4 to 72 hours after birth. This 2‐dose regimen has been shown to reduce MTCT by nearly 50%. We set out to demonstrate that in‐home HIV testing and NVP dosing by traditional birth attendants (TBAs) is feasible and acceptable by women in rural Zambia. Methods This was a pilot program using TBAs to perform rapid saliva‐based HIV testing and administer single‐dose NVP in tablet form to the mother at the onset of labor and syrup to the infant after birth. Results A total of 280 pregnant women were consented and enrolled into the program, of whom 124 (44.3%) gave birth at home with the assistance of a trained TBA. Of those, 16 (12.9%) were known to be HIV positive, and 101 of the remaining 108 (93.5%) accepted a rapid HIV test. All these women tested HIV negative. In the subset of 16 mothers who were HIV positive, 13 (81.3%) took single‐dose NVP administered by a TBA between 1 and 24 hours prior to birth and 100% of exposed newborns (16 of 16) received NVP syrup within 72 hours after birth, 80% of whom were dosed in the first 24 hours of life. Discussion With the substantial shortage of human resources in public health care throughout sub‐Saharan Africa, it is extremely valuable to utilize lay health care workers to help extended services beyond the level of the facility. Given the high uptake of PMTCT services we believe that TBAs with proper training and support can successfully provide country‐approved PMTCT.